Crystallization and preliminary x-ray characterization of a lectin from Cicer arietinum (chickpea) - Katre, Uma V.; Gaikwad, S. M.; Bhagyawant, S. S.; Deshpande, U. D.; Khan, Mohammad Islam; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2005)

Steady state and time-resolved fluorescence studies of a hemagglutinin from Moringa oleifera - Katre, Uma V.; Suresh, C. G.; Khan, Mohammad Islam; Gaikwad, Sushama M. (Journal of Fluorescence, 2008)
The saccharide binding and conformational characterization of a hemagglutinin, a low molecular weight protein from the seeds of Moringa oleifera was studied using steady state and time resolved fluorescence. The lectin binds sugars LacNAc (K-a = 1380 M-1) and fructose (K-a = 975 M-1), as determined by the fluorescence spectroscopy. It has a single tryptophan per monomer which is exposed on the surface and is in a strong electropositive environment as revealed by quenching with iodide. Quenching of the fluorescence by acrylamide involved both static (K-s = 0.216 M-1) and collisional (K-sv= 8.19 M-1) components. The native protein showed two different lifetimes, tau(1) (1.6 ns) and tau(2) (4.36 ns) which decrease and get converted into a single one, (2.21 ns) after quenching with 0.15 M acrylamide. The bimolecular quenching constant, k(q) was 7.55 x 10(11) M-1 s(-1). ANS binding studies showed that the native protein has exposed hydrophobic patches which get further exposed at extreme acidic or alkaline pH. However, they get buried in the interior of the protein in presence of 1 M GdnHCl or urea.
Keywords: ANS binding; fluorescence; Hemagglutinin; lifetime; Moringa oleifera; saccharide binding; Solute quenching

Structure-activity relationship of a hemagglutinin from Moringa oleifera seeds - Katre, Uma V.; Suresh, C. G.; Khan, Mohammad Islam; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2008)
The hemagglutinin from the seeds of Moringa oleifera (MoL) agglutinates human as well as rabbit erythrocytes; the affinity for the latter is almost 250 times more than that for the former. MoL was inhibited by glycoproteins namely thyroglobulin, fetuin and holotransferin indicating the complex sugar specificity of the lectin. The protein is a homodimer with molecular mass of 14 kDa, subunits (7.1 kDa) linked by the disulfide bond(s). The secondary structure elements of MoL area-helix, 28%; beta-sheet, 23%; turn 20% and unordered 28%. While the activity and secondary structure were not affected at extreme pH and high temperature, they were drastically affected in presence of dithiothreitol at and above pH 7.0, indicating that disulfide linkages hold the active conformation of the protein. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: disulfide linkages; Moringa oleifera hemagglutinin; Secondary structure

Features of homotetrameric molecular association in protein crystals - Katre, Uma V.; Suresh, C. G. (Acta Crystallographica Section D-Biological Crystallography, 2009)
The crystal structures of proteins showing homotetrameric association, a common feature observed in many lectins, have been analyzed in order to understand the characteristics of tetrameric association in terms of the arrangement of subunits and their biological significance. The analysis could group the tetramer units into the following four categories. (i) Tetrahedral molecules, in which the four monomers form a nearly perfect tetrahedral arrangement. The angle between the axes of any two monomers is similar to 109 degrees. (ii) Molecules that form a sandwiched dimer of dimers in which the two dimers are arranged perpendicular to each other, one upon the other. (iii) Planar molecules, in which the four monomers lie in one plane and the corresponding sides of adjacent monomers face in opposite directions. This can be considered as a flattened tetrahedral shape. (iv) Planar closed molecules, in which all four monomers lie in one plane arranged in a head-to-tail fashion in a square. The first group and its variant, the third group, are the most commonly found arrangements in crystal structures. Each arrangement has its own importance for biological function. Some tetrameric assemblies that deviate from the majority described above also have relevance to their biological function.

Crystal structure of a plant albumin from cicer arietinum (chickpea) possessing hemopexin fold and hemagglutination activity - Sharma, Urvashi; Katre, Uma V.; Suresh, C. G. (Planta, 2015)
Crystal structure of a reported PA2 albumin from Cicer arietinum shows that it belongs to hemopexin fold family, has four beta-propeller motifs and possesses hemagglutination activity, making it different from known legume lectins. A plant albumin (PA2) from Cicer arietinum, presumably a lectin (CAL) owing to its hemagglutination activity which is inhibited by complex sugars as well as glycoproteins such as fetuin, desialylated fetuin and fibrinogen. The three-dimensional structure of this homodimeric protein has been determined using X-ray crystallography at 2.2 in two crystal forms: orthorhombic (P2(1)2(1)2) and trigonal (P3). The structure determined using molecular replacement method and refined in orthorhombic crystal form reached R-factors R (free) 22.6 % and R (work) 18.2 % and in trigonal form had 22.3 and 17.9 % in the resolution range of 20.0-2.2 and 35.3-2.2 , respectively. Interestingly, unlike the known legume lectin fold, the structure of this homodimeric hemagglutinin belonged to hemopexin fold that consisted of four-bladed beta-propeller architecture. Each subunit has a central cavity forming a channel, inside of which is lined with hydrophobic residues. The channel also bears binding sites for ligands such as calcium, sodium and chloride ions, iodine atom in the case of iodine derivative and water molecules. However, none of these ligands seem important for the sugar recognition. No monosaccharide sugar specificity could be detected using hemagglutination inhibition. Chemical modification studies identified a potential sugar-binding site per subunit molecule. Comparison of C-alpha atom positions in subunit structures showed that the deviations between the two crystal forms were more with respect to blades I and IV. Differences also existed between subunits in two forms in terms of type and site of ligand binding.
Keywords: Beta-propeller fold; Chemical modification; Chickpea lectin; Complex sugars; PA2 albumin; Sugar binding